1983
DOI: 10.3109/17453678308996623
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Dislocations of the Sternoclavicular Joint

Abstract: Six patients with dislocation of the sternoclavicular joint are presented. Their main complaints were chronic recurrent spontaneous dislocation and local tenderness and discomfort during normal use of the shoulder. Two patients were treated according to Brown's modified procedure while four patients were operated with Burrow's technique. Ten weeks immobilization postoperatively is recommended to obtain a satisfactory result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…Satisfactory results were reported with the use of Burrows procedure for chronic recurrent sternoclavicular joint dislocations. 1 Resection of the medial end of the clavicle is an option in treating painful sternoclavicular joints. Eskola et al 6 found poor results in patients treated with resection of the medial end of the clavicle for old traumatic dislocations and reported good results with tendon grafts and fascial loops.…”
Section: Discussionmentioning
confidence: 99%
“…Satisfactory results were reported with the use of Burrows procedure for chronic recurrent sternoclavicular joint dislocations. 1 Resection of the medial end of the clavicle is an option in treating painful sternoclavicular joints. Eskola et al 6 found poor results in patients treated with resection of the medial end of the clavicle for old traumatic dislocations and reported good results with tendon grafts and fascial loops.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The instability can be anterior, superior or posterior and may occur acutely or chronically. In acute presentations, stability can be successfully restored with sutures through the bone, bone anchors 7,8 or other techniques.…”
mentioning
confidence: 99%
“…Firstly, by direct force from impact against the steering wheel, or the effect of a seat belt [2, 9-11, 15, 18, 19]; these fractures occur mainly at the level of the sternal body with posterior displacement. Secondly, by flexion-compression with the head thrust forward with forced flexion at the cervicothoracic junction, resulting in a fracture of the manubrium, or a fracture between it and the body of the sternum, and frequently associated with vertebral body compression [6] and thirdly, by lateral application of force to the shoulder which usually dislocates the sternoclavicular joint, but without an associated fracture [1,4,8,16,21]. This was the mechanism in our case.…”
Section: Introductionmentioning
confidence: 65%